2017
DOI: 10.3389/fnhum.2017.00218
|View full text |Cite
|
Sign up to set email alerts
|

Slow and Fast Responses: Two Mechanisms of Trial Outcome Processing Revealed by EEG Oscillations

Abstract: Cognitive control includes maintenance of task-specific processes related to attention, and non-specific regulation of motor threshold. Depending upon the nature of the behavioral tasks, these mechanisms may predispose to different kinds of errors, with either increased or decreased response time (RT) of erroneous responses relative to correct responses. Specifically, slow responses are related to attentional lapses and decision uncertainty, these conditions tending to delay RTs of both erroneous and correct r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 71 publications
(202 reference statements)
5
30
0
1
Order By: Relevance
“…In the current study, beta oscillations were relatively low in frequency (12–20 Hz) and late in time (700–1000 ms) compared to previous studies ( Marco-Pallerés et al, 2008 , 2015 ; HajiHosseini et al, 2012 ; Leicht et al, 2013 ; Mas-Herrero et al, 2015 ; see Luft, 2014 for review). To date, only few studies investigating feedback processing have reported an increase in low beta power at around 800 ms ( HajiHosseini et al, 2012 ; Leicht et al, 2013 ; Luft, 2014 ; Pornpattananangkul and Nusslock, 2016 ; Novikov et al, 2017 ). For example, when comparing low to high probable rewards HajiHosseini et al (2012) revealed an increase in low beta power between 700 and 000 ms, resembling a similar pattern of activity in the current experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, beta oscillations were relatively low in frequency (12–20 Hz) and late in time (700–1000 ms) compared to previous studies ( Marco-Pallerés et al, 2008 , 2015 ; HajiHosseini et al, 2012 ; Leicht et al, 2013 ; Mas-Herrero et al, 2015 ; see Luft, 2014 for review). To date, only few studies investigating feedback processing have reported an increase in low beta power at around 800 ms ( HajiHosseini et al, 2012 ; Leicht et al, 2013 ; Luft, 2014 ; Pornpattananangkul and Nusslock, 2016 ; Novikov et al, 2017 ). For example, when comparing low to high probable rewards HajiHosseini et al (2012) revealed an increase in low beta power between 700 and 000 ms, resembling a similar pattern of activity in the current experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of the specific frequency band, latency interval, and electrode positions was purely data-driven and based on statistical analysis of the ERSP data averaged over the experimental conditions (the analysis was orthogonal to our main analysis). The ERSP data was tested against zero using permutational statistics on t-score maps transformed with the TFCE (threshold-free cluster enhancement) algorithm (see Novikov et al, 2015 , 2017 for prior examples; also see Smith and Nichols, 2009 ). For more details, see Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%
“…However, there is some literature on how the type of incorrect response is an indication for response time and for the underlying processes. For example, Novikov et al (2017) hypothesize based on the literature that errors either stem from lack of cognitive control (deemed to be premature responses) and would lead to short response times (error speeding) or from attentional lapses and uncertainty. The study by Novikov et al (2017) concerns an auditory discrimination task and the use of EEG to locate oscillations in different regions of interest in the brain.…”
Section: Response Time Modelsmentioning
confidence: 99%
“…For example, Novikov et al (2017) hypothesize based on the literature that errors either stem from lack of cognitive control (deemed to be premature responses) and would lead to short response times (error speeding) or from attentional lapses and uncertainty. The study by Novikov et al (2017) concerns an auditory discrimination task and the use of EEG to locate oscillations in different regions of interest in the brain. On average the response times were shorter for correct responses than for incorrect responses, a common finding for complex attentional tasks (Wilding, 1971; Luce, 1986) and slow errors are found to be an indication of attentional lapses and uncertainty.…”
Section: Response Time Modelsmentioning
confidence: 99%
“…The condensation task, which we used both in our previous studies (Novikov et al, 2015, 2017) and in the current study, is different from the aforementioned classical tasks as it implies a complex S-R mapping rule that involves feature conjunctions rather than single stimulus features(Posner, 1964; Gottwald and Garner, 1975). Our task involves two features with two levels each, and both features should be accounted for simultaneously in order to select a correct response from two possibilities; none of the features alone is enough to solve the task.…”
Section: Introductionmentioning
confidence: 95%